(untitled) - Lewine, Donald A. (Sebastopol, Calif, 1992)
This guide, intended as an explanation of the POSIX standard and as a reference for the POSIX.1 programming library, helps you write more portable programs. Most UNIX systems today are POSIX compliant because the federal government requires it for its purchases. Even OSF and UI agree on support for POSIX.Unfortunately, given the manufacturer's documentation, it can be difficult to distinguish system-specific features from those features defined by POSIX.
Keywords: POSIX (Computer software standard),POSIX (Chuẩn phần mềm máy tính)